Answer:
$6488.19
Step-by-step explanation:
To solve this problem we use the compounded interest formula:
![amount = principal(1 + (r \n))^({n}{t})](https://tex.z-dn.net/?f=amount%20%20%3D%20%20principal%281%20%2B%20%28r%20%5Cn%29%29%5E%28%7Bn%7D%7Bt%7D%29)
a = $2600(1+(0.0675/1))¹*¹⁴
a = $6488.19
Answer:
(-7.5, 3.5)
Step-by-step explanation:
![midpoint \: = ( \frac{x1 + x2}{2} \: , \: \frac{y1 + y2}{2} )](https://tex.z-dn.net/?f=midpoint%20%5C%3A%20%20%3D%20%28%20%5Cfrac%7Bx1%20%2B%20x2%7D%7B2%7D%20%5C%3A%20%20%2C%20%5C%3A%20%20%5Cfrac%7By1%20%2B%20y2%7D%7B2%7D%20%29)
![= ( \frac{ ( - 5) + ( - 10)}{2} , \frac{(5) + (2)}{2} )](https://tex.z-dn.net/?f=%20%3D%20%28%20%5Cfrac%7B%20%28%20-%205%29%20%2B%20%28%20-%2010%29%7D%7B2%7D%20%2C%20%5Cfrac%7B%285%29%20%2B%20%282%29%7D%7B2%7D%20%29)
![= ( \frac{ - 15}{2} , \frac{7}{2} )](https://tex.z-dn.net/?f=%20%3D%20%28%20%5Cfrac%7B%20-%2015%7D%7B2%7D%20%2C%20%5Cfrac%7B7%7D%7B2%7D%20%29)
![= ( - 7.5,3.5)](https://tex.z-dn.net/?f=%20%3D%20%28%20-%207.5%2C3.5%29)
Answer:
(4, -3)
Step-by-step explanation:
Answer:
(-4x - 2)(-5x) + (-4x - 2)(3)
Step-by-step explanation:
Your polynomial is
(-4x - 2)(-5x + 3)
The distributive property states that
a(b + c) = ab + ac
Let a = -4x - 2. Then
(-4x - 2)(-5x + 3) = a(5x + 3) = a(-5x) + a(3)
Substitute the value of a.
a(-5x) + a(3) = (-4x - 2)(-5x) + (-4x - 2)(3)
You have just distributed the first binomial (-4x - 2) among the terms of the second binomial.
1/2 of the beads will be blue, and 1/2 of them would be red Hope this helped!